Electronic structure of metal quinoline molecules from G0W0 calculations - Sanvito, Stefano; Droghetti, Andrea (My University, 2014)
The photoemission spectra of four different metal quinoline molecules, namely, the prototypical tris(8-hydroxyquinolinato)-aluminum(III) (Alq3) complex and the related compounds Gaq3,Inq3, and tris-(9-hydroxyphenalen-1oate)-aluminum(III) [Al(OP)3] are compared to the electronic structure computed with different first-principles methods. In general, we found that, for Alq3,Gaq3, and Inq3, the molecular orbitals obtained with density functional theory and hybrid functionals represent a good approximation to the quasiparticle states. The same conclusion can be partially extended to the interesting case of Al(OP)3, although a direct comparison between theoretical and experimental results appears rather difficult for states, which are lower in energy than the first ten highest occupied molecular orbitals. Taking our results as a starting point we critically discuss the different available experimental data concerning the charge transport gap of Alq3.
PUBLISHED
Keywords: organic semiconductors (OSCs); Nanoscience & Materials